Prompt clinical and electrophysiological remission of refractory peripheral neuropathy in long-standing rheumatoid arthritis with tocilizumab: a case report - Huang, Hai; Zhong, Xuexian; Kuang, Shan; Tan, Jinhui; Tan, Linghua; Li, Bo (Frontiers in Immunology, 2026)
Peripheral neuropathy (PN) is a debilitating extra-articular manifestation of rheumatoid arthritis (RA), frequently driven by chronic inflammation and vasculitis. Its management remains challenging owing to limited evidence and the adverse effects associated with long-term glucocorticoids (GCs) use. We present a 48−year−old woman with 21-year seropositive RA who developed severe, progressive PN manifesting as multifocal asymmetric sensorimotor deficits. Electrophysiology confirmed axonal damage, and cerebrospinal fluid (CSF) showed albuminocytologic dissociation. Previous therapies, including methotrexate, etanercept, and tofacitinib, failed to control neuropathy. During a severe flare with high inflammatory markers, she received intravenous methylprednisolone followed by the interleukin-6 (IL-6) receptor antagonist tocilizumab. Within days, neuropathic symptoms and arthritis improved. After 12 months of monthly tocilizumab, inflammatory markers normalized, and repeat nerve−conduction studies demonstrated significant recovery. This case highlights that tocilizumab, by targeting the IL-6 pathway pivotal to RA-associated vasculitis and systemic inflammation, can induce rapid remission of refractory PN while facilitating glucocorticoid tapering. It supports the use of biologic agents with distinct mechanisms in managing complex extra−articular RA.